Economic Leading Sectors And Competitiveness In South Tapanuli Regency - tulus situmorang; Ketut Sukiyono; Sriyoto Sriyoto (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2020)
This study aims to determine the economic leading sectors, determine the position of the ecoomic leading sectors Agriculture sector specially and the priority sectors in the economic developement in South Tapanuli Regency. The data used is secondary data of the Gross Domestic Regional Bruto year 2011 to 2018 obtained from the Central Bureau of Statistic. Location Quotient (LQ), Dynamic Location Quotient (DLQ) , Shift-share, and Overlay analysis were applied in this research. The result of the analysis showed that the economic leading sectors in Souths Tapanuli regency are Transportation and Warehousing sector, Other Services Activities, Agriculture, Forestry, and Fishing, Manufacturing, and Electricity and Gas sector. These sectors are also a priority order to be developed. The study also showed that the Agriculture, Forestry and Fisheries sector is one of the leading sector with description: not progressive and weak competitiveness.